Mengasihi Musuh Berdasar Analisis Pemikiran Filsafat Tentang Intersubjektivitas: Loving Enemies Based on Philosophical Thought Analysis on Intersubjectivity - Apriano, Alvian; Naupal, Naupal; Hadinata, Fristian (Jurnal Filsafat Indonesia, 2025)
Loving one's enemy is a "philosophical instruction" that is difficult to practice in daily life. The level of difficulty varies depending on the scars left by the relationships that give rise to enmity. Intuitively, this practice appears highly contradictory, but philosophically, its seeds require special attention, as philosophy recognizes the principle of doing good and beneficial acts for others, even when there is no reciprocal exchange for what has been given. The question that arises is, "Which philosophical thought can initiate a discourse on loving one's enemy, and from it, what daily steps can be derived as a concrete practice of loving one’s enemy?" Gabriel Marcel's thoughts on intersubjectivity can begin a practical discourse on loving one’s enemy because the subject, that is, the individual, inherently needs to relate to the world. Naturally, the relationship sought is a constructive one, as reflected in his philosophical idea of esse est co-esse or being is being-with, which he introduces as existence together in the world. This paper aims to provide a philosophical assessment of the difficulty of loving one’s enemy based on Gabriel Marcel's philosophical thoughts on intersubjectivity, so that a philosophical practice in daily life can be realized to end enmity and build more productive relationships.